Anthropometric measurements, sexual development and serum reproductive hormonal levels among boys in the rural Western Cape - Mao, Jun (Institute of Infectious Disease and Molecular Medicine, 2016)
Background: Our previous epidemiological study have investigated the effect of pesticides on growth of boys in the Western Cape rural area, in this cross-sectional study, we extend those initial observation into a more detailed exploration of t he growth pattern in anthropometric variables and hormonal indicators, and its relation to pubertal stage. Reference data in relation to pubertal stage are presented, and compared with other international findings. Objective: To investigate the anthrop ometric growth and reproductive hormones alternation of Western Cape Rural boys who are potentially exposed to agricultural pesticides. Methods: A cross-sectional study of 269 boys was conducted in the rural Western Cape in South Africa. Tests included serum gonadotrophin releasing hormone (GnRH), lutenizing hormone (LH), follicle stimulating hormone (FSH), testosterone, sex hormone binding globulin (SHBG) and estradiol (E2); a physical examination of height, weight and BMI measurements; sexual matura tional assessment and a questionnaire (demographics and general medical history). Median of anthropometric variables and hormone levels by pubertal stage were compared with international references. Results: Median age of pubertal onset is 11.6 years old, later than African American boys and Urban South African boys. Western Cape rural boys were apparently shorter and lighter compared with the CDC and the WHO growth standards in the prepubertal and early pubertal stage, and then catch-up evidently in the mid and late puberty. Compared with previous pubertal hormonal studies, our boys were low in serum levels of testosterone were low and high in oestradiol levels throughout entire pubertal stages and the classic endocrine Negative Feedback Loops in hy pothalamic pituitary gonadal axis were established earlier. Conclusion: The results provide further evidence for the effects potentially from agricultural pesticides exposure in the pattern of growth in height and weight, and hormonal fluctuations dur ing the development of puberty.